Combination of NPK fertilizer with bokashi rice straw on growth and yield of Cisantana rice varieties - Akram Boga; Herwin Yatim (Faculty of Agriculture, Tompotika Luwuk University, 2021)
One of the cultivation technologies that need to be considered in increasing rice production is the proper use of fertilizer. This study is to find out the substitution of NPK fertilizer with rice straw bokashi to the growth and yield of rice paddy plants cisantana varieties. This research was conducted from August to November 2020 in Samaku Village, Bualemo District, Banggai Regency. The method used is a RandomIzed Design Group (RAK) factorial pattern consisting of 2 factors, namely factor A (NPK fertilizer) and factor B (Straw Bokashi). The combination of NPK fertilizer and rice straw bokashi has no natural effect on rice paddy plants of Cisantana varieties. Still, it has a natural impact on grain dry weight per plot. The treatment of rice straw bokashi independently has a noticeable effect on the height of the plant, the number of saples, the number of productive saples and the length of the panic. The bokashi straw rice dose of 75% (3.75 tons/ha) is the best dose for high plant growth, number of saples, number of productive saples and malai length. While the dose of 75% NPK (187.5 kg/ha) + 75% bokashi rice straw (3.75 tons/ha) is the best combination dose for varied dry weight of grain per plot.